Proteoglycans and Amyloidogenic Proteins in Peripheral Amyloidosis - Gervais, Francine; Morissette, Celine; Kong, Xianqi (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2003)
Amyloidogenic proteins have the characteristic of adopting a β-sheet conformation and assembling into fibrils. Although similar in fibrillar appearance, each type of peripheral amyloid deposits differs in the nature of the amyloidogenic protein forming fibrils. Other elements, known as the common structural elements of the amyloid deposits, also contribute to amyloidogenic process in vivo. Among these elements, heparan sulfate proteoglycans (HSPGs) have been shown to bind to different types of amyloidogenic proteins and to promote the formation of β-sheet secondary structure. Once fibrils are formed, HSPGs protect the fibrils from proteolytic degradation, which lead to the accumulation of the deposits in the targeted organs. Understanding the regulation of protein folding by proteoglycans can lead to the development of low molecular weight compounds, which bind to the amyloidogenic proteins prior to their organization as fibrils. Such binding would interfere with the natural association of amyloidogenic protein with HSPGs and maintain the amyloid protein in a non-fibrillar structure (either random coil or a mix of α-helix and β-sheet structure). It would also favor their clearance, and thereby inhibit or completely block the formation of amyloid deposits. Since HSPGs interact with several types of amyloidogenic proteins, such an approach may be beneficial for the treatment of systemic and localized types of amyloidosis.
Keywords: HSPGs